Alternative renin-angiotensin system pathways in adipose tissue and their role in the pathogenesis of obesity - Slamkova M (Sciendo, 2016)
Adipose tissue expresses all the renin-angiotensin system (RAS) components that play an important role in the adipogenesis, lipid and glucose metabolism regulation in an auto/paracrine manner. The classical RAS has been found to be over-activated during the adipose tissue enlargement, thus elevated generation of angiotensin II (Ang II) may contribute to the obesity pathogenesis. The contemporary view on the RAS has become more complex with the discovery of alternative pathways, including angiotensin-converting enzyme 2 (ACE2)/angiotensin (Ang)-(1-7)/Mas receptor, (pro)renin receptor, as well as angiotensin IV(Ang IV)/AT4 receptor. Ang-(1-7) via Mas receptor counteracts with most of the deleterious effects of the Ang II-mediated by AT1 receptor implying its beneficial role in the glucose and lipid metabolism, oxidative stress, inflammation, and insulin resistance. Pro(renin) receptor may play a role (at least partial) in the pathogenesis of the obesity by increasing the local production of Ang II in adipose tissue as well as triggering signal transduction independently of Ang II. In this review, modulation of alternative RAS pathways in adipose tissue during obesity is discussed and the involvement of Ang-(1-7), (pro)renin and AT4 receptors in the regulation of adipose tissue homeostasis and insulin resistance is summarized.